1999
DOI: 10.1007/bf02483026
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of perineal rectosigmoidectomy for the treatment of rectal prolapse in elderly and high-risk patients

Abstract: We report herein on the follow-up of ten consecutive patients who underwent perineal rectosigmoidectomy, and discuss the indications, surgical technique, and outcomes of this procedure. The median age of the patients was 79 years, with a range of 26 to 85 years, and eight patients had complicating medical conditions. Of five patients who underwent this procedure for a recurrent prolapse after another type of perineal procedure, four had previously undergone the Thiersch operation combined with the Gant-Miwa te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
37
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 7 publications
2
37
0
3
Order By: Relevance
“…66 Some authors 15,60,85,92,95 have therefore suggested the addition of levatorplasty to perineal rectosigmoidectomy. The advantage of posterior levatorplasty is that it recreates the anorectal angle, which seems to improve anal continence.…”
Section: Perineal Rectosigmoidectomymentioning
confidence: 99%
“…66 Some authors 15,60,85,92,95 have therefore suggested the addition of levatorplasty to perineal rectosigmoidectomy. The advantage of posterior levatorplasty is that it recreates the anorectal angle, which seems to improve anal continence.…”
Section: Perineal Rectosigmoidectomymentioning
confidence: 99%
“…This situation does not apply in cases of patients with rectal prolapse that does not have incontinence, there's no evidence of electromyographic pudendal nerve injury, so this theory is applicable only to patients with rectal prolapse and fecal incontinence. In addition, the relaxation of the lateral ligaments and the inertia of the pelvic floor muscles have been suggested as other causes for rectal prolapse [7]. The most common symptoms are bulging, bleeding, frequent defecation episodes, and rectal tenesmus.…”
mentioning
confidence: 99%
“…To resolve this problem, options approach abdominal and perineal surgical treatment. Historically, perineal approaches are associated with higher recurrence rates [7,8]. This higher recurrence rate is compensated with lower perioperative morbidity, especially in patients with multiple comorbidities, old or too weak to withstand the abdominal surgical approach [16].…”
mentioning
confidence: 99%
See 2 more Smart Citations